2022
DOI: 10.1002/we.2756
|View full text |Cite
|
Sign up to set email alerts
|

Loads assessment of a fixed‐bottom offshore wind farm with wake steering

Abstract: Wake steering via deliberate yaw offset is an emerging wind farm control technique that has the potential to mitigate wake losses and further increase wind farm energy yield. The loads impact of this technique has been studied, but there is limited insight into wind‐farm‐wide impacts of wake steering. Understanding such impacts is crucial to determining the feasibility of using wake steering in commercial wind farms. To that end, this work investigates the impacts of wake steering on the loads of all turbine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…A direct outcome of this work is to enable aeroservoelastic simulations of turbines operating in the observed conditions and validate predictions of wake-steering loads. This is detailed in the companion paper by Shaler et al (2023), which compares the simulated response of turbines T2 and T3 with SCADA signals and available loads measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A direct outcome of this work is to enable aeroservoelastic simulations of turbines operating in the observed conditions and validate predictions of wake-steering loads. This is detailed in the companion paper by Shaler et al (2023), which compares the simulated response of turbines T2 and T3 with SCADA signals and available loads measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A study period was identified based on the availability of both quality controlled lidar wind and loads data (for the study of Shaler et al (2023)). The availability of lidar data was considered essential for this study because the lidar captures more inflow characteristics than point measurements of wind conditions.…”
Section: Case Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid extreme yaw misalignments, we constrain the lower and upper yaw offset bounds to −25° and +25°, respectively. Note that in practice, further reducing the magnitude of the yaw offset bounds as wind speed increases may be necessary to mitigate higher structural loads caused by yaw misalignment (Damiani et al, 2018;Shaler et al, 2022).…”
Section: Wake Steering Optimization Using Florismentioning
confidence: 99%
“…Wake steering has been central to many numerical [2,3,4] and wind tunnel [5,6] studies, leading to commercial field testing [7,8]. The benefits of increased wind farm power due to wake steering usually come at the expense of increased fatigue loads [9].…”
Section: Introductionmentioning
confidence: 99%